Microencapsulated Mixture of Fish Oil and Fortified in Ice Cream (Faculty of Animal Science Universitas Brawijaya, 2016)
In recent years there has been considerable efforts to rearrange fatty acids composition of dairy products to improve the long-term health of consumers. One of the efforts is to fortify essential fatty acids in ice cream. The objective of this study was to find out the fatty acids profile of either Selaroides spp, Clarias sp and Thunnus sp fish oil, microencapsulated fish oil and ice cream fortified with this fish oil mixture. Selaroides spp, Clarias sp and Thunnus sp used as raw material were obtained from Palu, Central Sulawesi. The study was caried out using Nested Block Design as the experimental design. The microencapsulated fish oil was prepared using freeze drying and spray drying method. The variables measured were fatty acids profile, microencapsulated fish oil and ice cream fortified with microencapsulated fish oil. The research results showed that SFA, MUFA and PUFA contents of fish oil mixture of Selaroides spp and Clarias sp using freeze drying method were 53.74%, 32.20% and 1.91%, while using spray drying method were 61.30%, 38.70% and 0% (not detected), respectively. It can be concluded that freeze drying method from the point of view of total PUFA is the best method for mincroencapsulation process of this fish oil mixture. Fortification of 15 g (w/w) microencapsulated fish oil in ice cream could reduced SFA and increased the MUFA and PUFA.